Lysine catabolism in Streptomyces spp. is primarily through cadaverine: beta-lactam producers also make alpha-aminoadipate. - Madduri, K (1989)
Genetic and biochemical evidence was obtained for lysine catabolism via cadaverine and delta-aminovalerate in both the beta-lactam producer Streptomyces clavuligerus and the nonproducer Streptomyces lividans. This pathway is used when lysine is supplied as the sole source of nitrogen for the organism. A second pathway for lysine catabolism is present in S. clavuligerus but not in S. lividans. It leads to alpha-aminoadipate, a precursor for beta-lactam biosynthesis. Since it does not allow S. clavuligerus to grow on lysine as the sole nitrogen source, this pathway may be used exclusively to provide a precursor for beta-lactam biosynthesis. beta-Lactam producers were unable to grow well on alpha-aminoadipate as the only nitrogen source, whereas three of seven species not known to produce beta-lactam grew well under the same conditions. Lysine epsilon-aminotransferase, the initial enzyme in the alpha-aminoadipate pathway for lysine catabolism, was detected in cell extracts only from the beta-lactam producers. These results suggest that synthesis of alpha-aminoadipate is exclusively a secondary metabolic trait, present or expressed only in beta-lactam producers, while genes governing the catabolism of alpha-aminoadipate are present or fully expressed only in beta-lactam nonproducers.